2004
DOI: 10.1111/j.0023-5962.2004.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of the FIFA Football Worldcup

Abstract: Summary The expansion of economics to ‘non‐market topics’ has received increased attention in recent years. The economics of sports (football) is such a sub‐field. This paper reports empirical evidence of team and referee performances in the FIFA World Cup 2002. The results reveal that being a hosting nation has a significant impact on the probability of winning a game. Furthermore, the strength of a team measured with the FIFA World Ranking does not play the important role presumed, which indicates that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 10 publications
3
59
1
4
Order By: Relevance
“…Mechtel et al [25] also identified strength (points earned in the last three seasons) and home advantage as success factors. Torgler [58] applied an economic win function to determine the influences on winning or not winning during the FIFA World Cup 2002. He showed that a higher number of shots on goal leads to a higher probability to win.…”
Section: Predictive Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechtel et al [25] also identified strength (points earned in the last three seasons) and home advantage as success factors. Torgler [58] applied an economic win function to determine the influences on winning or not winning during the FIFA World Cup 2002. He showed that a higher number of shots on goal leads to a higher probability to win.…”
Section: Predictive Analysesmentioning
confidence: 99%
“…Hosting the tournament was a strong advantage as well. It increases the chance of winning by 45 percentage points [58]. Hanau, Wicker and Soebbing [59] investigated the difference between the expected outcome of a football match and the actual outcome.…”
Section: Predictive Analysesmentioning
confidence: 99%
“…4 Greece is a European country but is not generally regarded as a most developed one in football. 5 It must be noted that striking result of World Cup 2002 held in Japan-Korea was significantly the result of a home advantage (Torgler 2004). Nevertheless, Euro2004 and 2008 were held in Portugal and Austria-Switzerland, respectively, leading me to assume that a home for Greece and Turkey.. 6 Italy"s Serie A, England"s Premiership, Germany"s Bundesliga, and Spain"s Primera Division.…”
Section: Review Of Changes In Fifa Worlid Raking Pointsmentioning
confidence: 99%
“…According to the above related content wedesigned the questionnaires. In order to ensure the scientific nature of the questionnaire, we also had asked relevant experts on the questionnaire made a change, and finally formating a formal questionnaire [12]. The initial preparation of the campus football, including the spirit of culture, material culture, institutional culture and behavioral culture 4 first-class indicators, 8 secondary indicators, 30 three indicators ( fig.2).…”
Section: Interview Methodsmentioning
confidence: 99%